Levelized Electricity Cost of Five Solar Photovoltaic Plants of Different Capacities. (2016) - Bano, Tahira; Rao, K.V.S.
Abstract: This paper deals with the calculation of Levelized Electricity Cost (LEC) of five Solar Photovoltaic power (SPV) plants of different capacities 1MW, 5MW, 10MW, 25MW and 130MW. The calculation has been performed from the power generated data of the year 2014. The effect of different parameters like interest rate, inflation rate, deprecation time (plant life) and cumulative utilization factor (CUF), on LEC have been analyzed. A comparative study of the plants is done by varying these parameters. Operation and maintenance cost has been assumed 1% of the capital cost. It has been observed that LEC increases with increase in both inflation rate and interest rate. However, the influence of inflation rate on LEC is more. LEC decreases with increase in plant life and cumulative utilization factor. SPV plants established earlier have higher LEC compared to that of plants established later due to reduction in cost of SPV module prices over the years.